Effect of impact angle on wear behavior of Mo2NiB2–Ni cermets with different Ni content. Issue 12 (15th June 2022) - Zhang, Lei; Huang, Zhifu; Jie, Wanqi; Cao, Zhen; Liu, Yangzhen; Zhou, Lian
Abstract: Herein, the influence of the impact angle and Ni content on the wear behavior of Mo2 NiB2 –Ni cermets was studied using an erodent-carrying slurry comprising artificial seawater and SiO2 sands. The results reveal that the material loss may be attributed to the wear damage caused by SiO2 sands because cermets are expected to exhibit good corrosion resistance in artificial seawater. The relative density of cermets markedly influences their resistance to wear damage, and the material loss experienced by cermets with poor relative density is 2–4 times higher than that of cermets with good relative density; this occurs because a higher relative density can markedly enhance the mechanical properties and reduce the defects in the cermets. Moreover, the results indicate that as the impact angle increases from 0° to 60°, the manifestation of the wear mechanism changes from damaging the Ni binder phase (caused by single cutting wear) to damaging both the Mo2 NiB2 ceramic and Ni binder phases due to the combination of cutting wear and impact wear. The wear damage is dominated by the cutting wear and impact wear from SiO2 sand at the low and high impact angles, respectively. Furthermore, the severe deterioration of the single ceramic skeleton at high impact angles indicates that the synergistic influence of the Mo2 NiB2 ceramic and Ni binder phases on enhancing the wear resistance of the cermets intensifies at high impact angles.